2018
DOI: 10.1080/15384101.2018.1464852
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of functional myogenic specification ofBona Fidemultipotent adult cardiac stem cells

Abstract: Ischemic Heart Disease (IHD) remains the developed world's number one killer. The improved survival from Acute Myocardial Infarction (AMI) and the progressive aging of western population brought to an increased incidence of chronic Heart Failure (HF), which assumed epidemic proportions nowadays. Except for heart transplantation, all treatments for HF should be considered palliative because none of the current therapies can reverse myocardial degeneration responsible for HF syndrome. To stop the HF epidemic wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(85 citation statements)
references
References 172 publications
0
85
0
Order By: Relevance
“…We demonstrated that SP promoted the stem cell properties of NK 1 R-expressing c-Kit + GATA4 + Nkx2.5 + /CD45 -cTnI -CPCs, which in turn was associated with high expression of pluripotency genes. It is well known that c-Kit and GATA4 expression is necessary and su cient for cardiac recovery [2]. In the case of c-Kit-activated transgenic mice, activated c-Kit receptors can improve cardiac recovery after cryoinjury [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We demonstrated that SP promoted the stem cell properties of NK 1 R-expressing c-Kit + GATA4 + Nkx2.5 + /CD45 -cTnI -CPCs, which in turn was associated with high expression of pluripotency genes. It is well known that c-Kit and GATA4 expression is necessary and su cient for cardiac recovery [2]. In the case of c-Kit-activated transgenic mice, activated c-Kit receptors can improve cardiac recovery after cryoinjury [2].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that c-Kit and GATA4 expression is necessary and su cient for cardiac recovery [2]. In the case of c-Kit-activated transgenic mice, activated c-Kit receptors can improve cardiac recovery after cryoinjury [2]. CD45c-Kit + isolated/cultured cardiac stem cells (CSCs) derived from the c-Kit-activated transgenic mice promote CSC activation and differentiation in vitro through Akt pathways [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations